2022
DOI: 10.1002/hbm.26026
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the regional substrates predictive of Alzheimer's disease progression through a convolutional neural network model and occlusion

Abstract: Progressive brain atrophy is a key neuropathological hallmark of Alzheimer's disease (AD) dementia. However, atrophy patterns along the progression of AD dementia are diffuse and variable and are often missed by univariate methods. Consequently, identifying the major regional atrophy patterns underlying AD dementia progression is challenging. In the current study, we propose a method that evaluates the degree to which specific regional atrophy patterns are predictive of AD dementia progression, while holding a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…Recently, some studies have shown that models trained by NC and AD outperform those trained by sMCI and pMCI for predicting the progression of MCI [4], [8], [7], [9], [10], [23]. Huang et al proposed a novel CNN to fuse the multi-modality information from T1-MRI and FDG-PET images around the hippocampus area for predicting MCI progression [4].…”
Section: A Progression Prediction Of MCImentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, some studies have shown that models trained by NC and AD outperform those trained by sMCI and pMCI for predicting the progression of MCI [4], [8], [7], [9], [10], [23]. Huang et al proposed a novel CNN to fuse the multi-modality information from T1-MRI and FDG-PET images around the hippocampus area for predicting MCI progression [4].…”
Section: A Progression Prediction Of MCImentioning
confidence: 99%
“…However, prospectively acquiring MCI subtype data is time-consuming and resource-intensive, which leads to relatively small labeled datasets, resulting in amplified overfitting and challenges in extracting discriminative information for real-world scenarios. Recently, some previous studies revealed that the models trained by NC and AD data perform better than those trained by sMCI and pMCI data for predicting the progression of MCI [4], [8], [9], [10]. However, these studies only considered that differences between sMCI and pMCI are analogical to those between NC and AD, ignoring the global ordinal nature of AD progression.…”
Section: Introductionmentioning
confidence: 99%
“…Early involvement of these regions in AD pathogenesis is well documented (35)(36)(37). Moreover, atrophy in the hippocampus and adjacent early Braak regions is predictive of conversion from MCI to AD (38,39). Association between tau and atrophy in regions corresponding to early Braak stages are also evident in Aβ-CN individuals (40), however the current results demonstrate that coupling was stronger when Aβ load was greater.…”
Section: Discussionmentioning
confidence: 48%
“…Here, the 531 of the 638 sMRI images of AD subjects are selected for the experiment, because the remaining 107 images have no corresponding MMSE values. We explore the frequent item-sets consisting of the neurodegenerative regions in each level (normal: MMSE ∈ [27,30]; mild: MMSE ∈ [21,26]; moderate: MMSE ∈ [10,20]; severe: MMSE ∈ [0, 9]) to analyze the process of neurodegeneration at different stages of AD. As summarized in Table 7, in the early stage of cognitive impairment (MMSE ∈ [27,30]), L.mAmyg and L.NAC have been neurodegenerative in most (over 83%) AD sMRI images.…”
Section: The Dl-extracted Neuroimaging Biomarker (P-score) Facilitate...mentioning
confidence: 99%
“…[19] The situation might be a reason why little attention has been paid to analyzing patterned pathological progression in AD based on DL models rather than targeting diagnostic classification tasks. [20][21][22][23] Some studies have started to extract atrophy features [24] or patterns [25] from sMRI to derive the brain age. In line with this effort, our recent study [26] has developed a DL model (2-dimensional convolutional neural network) to identify the critical discriminative brain regions for AD recognition.…”
Section: Introductionmentioning
confidence: 99%